Peran Keluarga yang Terpapar Covid-19 dalam Menguatkan Ketahanan Keluarga Perspektif Maqasid al-Shari’ah - Musyafaah, Nur Lailatul; Syafaq, Hammis; Musafa'ah, Suqiyah (Legitima : Jurnal Hukum Keluarga Islam, 2022)
During the Covid-19 pandemic, the family cluster was among the clusters that caused the spread of this virus. For families exposed to this virus, their family's resilience has been tested. This article discusses the resilience of families exposed to Covid-19 to be analyzed in maqasid al-shari’ah. The method used in this research is qualitative and field research. Data were collected through observation, interviews, and documentation. The collected data were analyzed as normative-descriptive. This study concluded that families exposed to Covid-19 work together to fight this virus by adjusting their respective conditions. For the mild, they self-isolate at home, and those with severe illnesses are hospitalized. If a family dies from Covid-19, the family left behind is isolated. What the family exposed to Covid does is maintain family resilience and maintain the physical and psychic health of the family. From the perspective of maqasid al-shari'ah, the effort corresponds to the concepts of hifz al-din (guarding religion), hifz al-nasl (guarding offspring), hifz al-nafs (guarding the soul), and hifz al-'aql (guarding reason).